Organisational identity construction on social media amidst COVID-19: the case of a Fast-Food Chain in Malaysia - Mazlin Azizan; Muhammad Zulfadhli Saifuddin; Najwa Zulkifli; Wardah Ismail (Penerbit Universiti Kebangsaan Malaysia, 2023)
for them to redefine their identities online for businesses to survive during trying times. This qualitative study examines the discourse strategies adopted by a popular fast-food chain in Malaysia, namely McDonald’s, in its postings on a social media platform during the pandemic. Through a hybrid analytical framework consisting of Critical Discourse Analysis and Politeness Theory, 79 postings on Facebook related to COVID-19 have been identified, coded and then examined using thematic analysis. The analysis found that McDonald’s adopted colloquialism, code-switching and linguistic politeness as its relational and localization strategies in communicating on Facebook. Further analysis also suggests that the organisation has utilised the social media platform consistently not only to keep the business afloat but also as an opportunity in expressing solidarity with and showing empathy towards Malaysians (for example, through COVID-19 hashtags like #safewithmekdi and #staysafe), creating a positive online organisational identity during the pandemic. This critical discourse study highlights the importance of altruistic values and prosocial behaviour in an organisation and hopes to shed light on the prominent role of linguistic strategies in online communication especially in managing a crisis.